ANALISA KEPUASAN WISATAWAN TERHADAP ATRIBUT DESTINASI WISATA RAJA AMPAT - Dina Michelle Parwestri (Tourism Retailing+, 2013)
The purpose of this study was to determine the attributes of tourism destination which play a dominant role in attracting tourists. This study also measures the satisfaction of the tourists of tourism attributes in Raja Ampat. This research use 80 respondents to be the sample, they are domestic and foreign tourists who travells to Raja Ampat. Data analysis technique applied  are descriptive analysis statistic means score, regression analysis, F-test, and normality test.Based on the result of this research, there are six attributes considered important by tourists, but there are 4 of the most dominant in attracting tourists to Raja Ampat.